The effect of muscle fatigue on instep kicking kinetics and kinematics in association football - Apriantono, T.; Nunome, H.; Ikegami, Y.; Sano, S. (Journal of Sports Sciences, 2006)
The aim of this study was to examine the effect of leg muscle fatigue on the kinetics and kinematics of the instep football kick. Fatigue was induced by repeated, loaded knee extension (40% body weight) and flexion (50% body weight) motions on a weight-training machine until exhaustion. The kicking motions of seven male players were captured three-dimensionally at 500 Hz before and immediately after the fatigue protocol. The significantly slower ball velocity observed in the fatigue condition was due to both reduced lower leg swing speed and poorer ball contact. The reduced leg swing speed, represented by a slower toe linear velocity immediately before ball impact and slower peak lower leg angular velocity, was most likely due to a significantly reduced resultant joint moment and motion-dependent interactive moment during kicking. These results suggest that the specific muscle fatigue induced in the present study not only diminished the ability to generate force, but also disturbed the effective action of the interactive moment leading to poorer inter-segmental coordination during kicking. Moreover, fatigue obscured the eccentric action of the knee flexors immediately before ball impact. This might increase the susceptibility to injury.